ICD 10: A Primer for the Orthopedic Foot and Ankle Surgeon. (September 2015) - Gonzalez, Tyler; Chiodo, Christopher
The use of the 10th Revision of the International Classification of Diseases (ICD-10) will likely be required as of October 2015. ICD-10 was developed to increase the specificity and accuracy of disease and injury reporting. The number of diagnostic codes in this system has increased substantially, and approximately half of all ICD-10 codes are related to the musculoskeletal system, whereas 25% of all codes are related to fractures. For most foot and ankle injuries, the new code structure includes location, laterality, degree of healing, and encounter type. At the provider level, navigating this system will initially be a complex task. Understanding the ICD-10 code structure, properly training appropriate staff, and financially preparing for implementation will minimize potential practice disruption.